Metabolic syndrome, adiponectin and proinflammatory status in patients with type 1 diabetes mellitus. (October 2014) - Timar, Romulus; Timar, Bogdan; Degeratu, Diana; Serafinceanu, Cristian; Oancea, Cristian
Objectives: To assess the prevalence of metabolic syndrome and evaluate proinflammatory status in patients with type 1 diabetes, and to analyse the relationship between inflammation, metabolic control and insulin resistance in these patients. Methods: Patients with type 1 diabetes were stratified according to the presence or absence of metabolic syndrome. Serum adiponectin, leptin, tumour necrosis factor (TNF)-α, interleukin (IL)-6 and high-sensitivity C-reactive protein (hsCRP) were quantified. Results: The prevalence of metabolic syndrome was 28.6% (22/77). Patients with metabolic syndrome had lower adiponectin concentrations and higher leptin, TNF-α, IL-6 and hsCRP concentrations compared with patients without metabolic syndrome. In addition, metabolic syndrome was associated with higher glycosylated haemoglobin and insulin dose, and increased insulin resistance. Conclusions: The proinflammatory state associated with metabolic syndrome in patients with type 1 diabetes leads to deterioration of glycaemic control and an increase in the required daily dose of insulin. Early and proactive diagnosis of metabolic syndrome in these patients will allow medication and lifestyle optimization, in order to prevent the occurrence of diabetes complications and improve health-related quality-of-life.